2019
DOI: 10.7554/elife.42299
|View full text |Cite
|
Sign up to set email alerts
|

More homogeneous capillary flow and oxygenation in deeper cortical layers correlate with increased oxygen extraction

Abstract: Our understanding of how capillary blood flow and oxygen distribute across cortical layers to meet the local metabolic demand is incomplete. We addressed this question by using two-photon imaging of resting-state microvascular oxygen partial pressure (PO2) and flow in the whisker barrel cortex in awake mice. Our measurements in layers I-V show that the capillary red-blood-cell flux and oxygenation heterogeneity, and the intracapillary resistance to oxygen delivery, all decrease with depth, reaching a minimum a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
125
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(160 citation statements)
references
References 136 publications
(288 reference statements)
33
125
2
Order By: Relevance
“…In contrast, the mean capillary RBC velocities were within the scopes of 0.1∼1.6 mm/s and 0.05∼0.9 mm/s as reported by Emmanuelle (Chaigneau et al, 2003) and Stefanovic et al (2008). In some other studies, the velocities in both anesthetized and awake mice were calculated to be approximately 0.7 or 1.3 mm/s (Huang et al, 2014;Wei et al, 2016;Li et al, 2019;Lu et al, 2019). Comparing to these values, our data seemed to be lower.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, the mean capillary RBC velocities were within the scopes of 0.1∼1.6 mm/s and 0.05∼0.9 mm/s as reported by Emmanuelle (Chaigneau et al, 2003) and Stefanovic et al (2008). In some other studies, the velocities in both anesthetized and awake mice were calculated to be approximately 0.7 or 1.3 mm/s (Huang et al, 2014;Wei et al, 2016;Li et al, 2019;Lu et al, 2019). Comparing to these values, our data seemed to be lower.…”
Section: Discussionsupporting
confidence: 52%
“…Comparing to these values, our data seemed to be lower. One possible reason may be due to the relatively smaller capillaries (with a mean diameter of 3.96 µm) we imaged than those imaged in prior studies (with mean diameters of 4.7 to 6 µm) (Li et al, 2019;Lu et al, 2019). Small vessels usually have lower RBC velocity.…”
Section: Discussionmentioning
confidence: 76%
“…Only very small differences can be observed for the occlusion of MSCs at different cortical depths ( Supplementary Figure 4a-d). These differences can probably be explained by a general decrease in flow rate over depth and a more homogeneous flow field for deeper cortical layers [39,46,49,50]. Moreover, our results suggest that the position of the MSC along the path between DA and AV does not play a significant role in the severity of the microstroke (Supplementary Figure 5).…”
Section: The Baseline Msc Flow Rate Increases the Area Of Impact Of Amentioning
confidence: 73%
“…It is well established that the oxygen partial pressure in capillaries shortly downstream of DAs is higher than in capillaries just upstream of AVs [50,51]. Moreover, it has been suggested that the tissue supplied by venule-sided capillaries might be more susceptible to hypoxia in the case of blood flow disturbances or during neural activation [51][52][53].…”
Section: The Minimum Distance Between An Arteriole-sided and A Venulementioning
confidence: 99%
“…Although transit time through capillaries should not be too heterogenous across depths, as this results in inefficient oxygen extraction (Jespersen and Østergaard, 2012), recent experimental and theoretical findings (Gutierrez-Jimenez et al, 2016;Schmid et al, 2017b) suggest that capillary transit time can increase with cortical depth. This means that also the baseline oxygen extraction fraction 0 may be slightly different between cortical depths both in the MV and AV (Li et al, 2019). While in the current implementation one can define depth-specific changes in oxygen metabolism (directly with ( ) or via ratio ), 0, can be specified within laminar BOLD signal equations (see derivation details in Supplementary Material 1).…”
Section: Limitations and Future Prospectsmentioning
confidence: 99%